Prevalence, Patterns, And Factors Associated With Excessive Smartphone Use Among University Students: A Cross-Sectional Study - R, Sreehari; C, Jayakumar; Natarajan, Gitanjali; Monsy, Edward; Varma, Parvathy (Journal of Neonatal Surgery, 2025)
Excessive smartphone use among students can lead to physical issues like sleep problems and muscle strain, as well as psychological issues including anxiety and depression, negatively affecting their academic performance. Objectives: The study investigated the prevalence and associated characteristics of excessive smartphone usage among college students in Kerala, South India. Method: The research included 1,030 participants chosen randomly from five different universities in Kerala through an online survey. The study collected information about participants' socio-demographic characteristics, smartphone usage patterns and their self-assessment of smartphone addiction. The Smartphone Addiction Scale—Short Version (SAS-SV) was used to assess the level of smartphone use. Results: The research showed that 36.7% of students demonstrated excessive smartphone use. The age of participants spanned between 18 and 24 years with an average of 20.50 years (SD = 1.66). The data showed that excessive smartphone usage was strongly related to habitual usage (r = 0.56, p <.001), process usage (r = 0.41, p <.001), and social usage (r = 0.21, p <.001). The results of multiple linear regression analysis revealed that habitual smartphone behaviour (β =.50, p <.001) and process usage (β =.13, p <.001) served as significant predictors which explained 33% of the addiction score variance. Conclusion: The research indicates that excessive smartphone use affects more than one-third of students and highlights the influence of habitual and entertainment-driven smartphone use on addiction levels. This demonstrates an urgent need for targeted intervention to promote digital wellness and mindful smartphone use in academic settings.